Nano-nanocomposites: an emerging class of materials. (14th April 2009) - Ayyub, Pushan
We review some of our recent results on nano-nanocomposites (NNC), which may be defined as a random, bi-phasic nanodispersion, i.e., where the characteristic size of both phases present is in nanometers. This is a subset of the larger family of nanocomposites, which commonly consist of one phase nanodispersed in an extended matrix phase. Such systems afford the possibility of tuning their physico-chemical properties via a large number of parameters, which include the nature of the components, the composition, and the size and morphology of both the phases. In certain especially interesting situations, the properties of the NNC are not simple linear superpositions of the properties of the individual nanocrystalline species. The three such special cases that are reviewed here include: NNCs of II-VI semiconductors with different band gaps that show enhanced photoluminescence, photoconductivity, and non-linear optical properties; NNCs of a superconductor and a normal metal, whose properties are predominantly controlled by the superconducting proximity effect; Metal-metal NNCs that are actually nanoscale, phase-separated alloys of 'immiscible' metals.